CGF Harmony facial skin revitalization for a 40+ patient (Journal of Face Aesthetics, 2018)
In facial skin revitalization it is important to use preventive measures and introduce minimally invasive treatments as soon as the first signs of ageing appear. Such treatments can include the administration of stem cells and concentrated growth factors (CGF Harmony). This procedure was used in the case presented in this paper. Its effects were assessed on the basis of medical photographic documentation obtained using the FotoMedicus system, and instrumental examination of skin parameters, phototype, hydration and redness by means of a Cutometer Dual MPA 580. CGF Harmony was applied three times, and after the second and third application an improvement in the majority of the assessed parameters was observed. However, it cannot be unequivocally demonstrated that three CGF Harmony applications are sufficient for 40+ patients; it may be necessary to monitor skin condition over a longer period of time and introduce combined treatments in the area of facial aesthetic medicine.
Keywords: face; skin parameters; medical photographic documentation; peeling; platelet rich plasma (PRP); stem cells CD34 and concentrated growth factors (CGF)